Discretionary Disclosure and External Financing. - Frankel, Richard; McNichols, Maureen; Wilson, G. Peter (The Accounting Review, 1995)
Focuses on the relationship between firms' tendencies to access capital markets and to disclose earnings forecasts. Disclosure tendencies of companies with external financing; Relation between management forecasts and analysts' expectations.